The epidemiological surveillance system: identifying processes: El sistema de vigilancia epidemiológica: identificando procesos - Oyola García, Alfredo (2018)
ABSTRACT Health systems are designed to improve the health of the population and therefore require rapid identification of the most relevant events that affect it. Given this, they have seen the obligation and need for establishing surveillance systems that must be optimized permanently; to do so, they must identify the processes that must be monitored and evaluated. Key words: Health systems; Epidemiological surveillance; Identification of processes.  (source: MeSH NLM) DOI: 10.25176/RFMH.v18.n3.1593